DOI: 10.20868/upm.thesis.47849
|View full text |Cite
|
Sign up to set email alerts
|

User profiles and adoption attributes of innovative bike-sharing systems: the case of BiciMAD (Madrid)

Abstract: Bike-sharing nowadays is a must-have element of the urban transport system that is changing mobility patterns in cities worldwide. BiciMAD, introduced in Madrid in June 2014, is an example of the latest generation (demand responsive multimodal systems), a unique technology at the moment of implementation and a new element in the urban mobility of Madrid. Impacts of BiciMAD on individual travel behaviour (mode choice, bicycle use, etc.) and urban mobility patterns (modal shift, number of trips, etc.) have also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 165 publications
(253 reference statements)
1
10
0
1
Order By: Relevance
“…Middle-aged people are also the majority of the users of car-sharing systems, and therefore they tend to compare BSSs to carsharing system in terms of efficiency and speed to reach their working destinations. This result is consistent with the cluster analysis results in Munkácsy & Monzón (2017), where students and inactive people were identified among the "fans" of the Madrid BSS, and with the factor analysis in Kim et al (2015), where age was found as a significant positive determinant of electric vehicle sharing program satisfaction in a sample where there were no respondents aged less than 20 years and respondents aged more than 59 years were only 0.2%. People having a tertiary degree are again more satisfied than less educated people (this is mainly due to the high percentage of positive responses to the Q14 question in the group of people having a high-level degree who in general are more sensitive to ecological issues than less educated people), whereas managers, self-employed workers and students are the most satisfied groups.…”
Section: Nlpca Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Middle-aged people are also the majority of the users of car-sharing systems, and therefore they tend to compare BSSs to carsharing system in terms of efficiency and speed to reach their working destinations. This result is consistent with the cluster analysis results in Munkácsy & Monzón (2017), where students and inactive people were identified among the "fans" of the Madrid BSS, and with the factor analysis in Kim et al (2015), where age was found as a significant positive determinant of electric vehicle sharing program satisfaction in a sample where there were no respondents aged less than 20 years and respondents aged more than 59 years were only 0.2%. People having a tertiary degree are again more satisfied than less educated people (this is mainly due to the high percentage of positive responses to the Q14 question in the group of people having a high-level degree who in general are more sensitive to ecological issues than less educated people), whereas managers, self-employed workers and students are the most satisfied groups.…”
Section: Nlpca Resultssupporting
confidence: 89%
“…Respondents declared to be interested in the introduction of such type of innovations with a positive response in 70% of the cases (question Q24). This is quite an opposite result compared to that obtained in the aforementioned BiciMAD survey where people mainly declared that they were not familiar with e-bikes and therefore did not appreciate the fact that all the BiciMAD bikes will be e-bikes (Munkácsy & Monzón, 2017). Respondents declared to be willing to pay a premium cost to use a more comprehensive service in 35% of cases (Question Q25).…”
Section: Survey Characteristics Data Collection and Exploratory Analmentioning
confidence: 78%
“…The future trend includes the integration of e-bikes to share and the project BiciMAD, introduced in Madrid (Span) in June 2014, includes 2028 electric bicycles distributed among 165 stations. Therefore, bike-sharing is also an emerging topic of urban transport and sustainable mobility related research [46]. This e-bike mobility will also be enhanced by bike lanes implemented in the cities [47].…”
Section: Discussionmentioning
confidence: 99%
“…A survey method developed by TRANSyT (Transport Research Centre, Universidad Politécnica de Madrid) [40,42], the combination of an intercept interview and an online questionnaire was used to ensure the desired number of complete responses by competent and encouraged respondents in an economic and easy-to-analyze manner. After a brief, 30-to 120-second long introduction of the topic and the incentives at a bike-sharing station to users or potential users (and some records, such as sex, age, place, time, and weather kept by surveyors), an access code to an online survey was provided.…”
Section: Methodology and Samplementioning
confidence: 99%
“…has been gathered. Previous outcomes of the project include a classification of potential users and nonusers [40] and an assessment of the impacts of bike-sharing on urban mobility and the use of bicycle [41] employing advanced statistic techniques of factorial and cluster analysis, as well as a study on the peculiarities of the adoption of bike-sharing as an innovation, applying the Theory of Diffusion of Innovations (under publication).…”
Section: Case Studymentioning
confidence: 99%